Perubahan Distribusi Produk Hasil Peternakan terhadap Media Digital dalam Pemenuhan Kebutuhan Konsumen di Era Pandemi di Beberapa Wilayah di Indonesia - Sari Putri Dewi (Jurnal Manajemen dan Organisasi, 2022)
Covid-19 outbreak has created a huge impact globally including in Indonesia. It impacted to almost of sectors including livestock industry. The limitation of mobility caused by the increasing number of positive cases of Covid-19 led to the consumer’s behavior changes especially the way they fulfill their daily basic needs. The digital platform helped the consumers to worry-free during the outbreak. It proven by the shifting of consumer’s behavior from offline activities such as visit to the wet and modern market to online activities to buy the basic needs from livestock product such as meat, eggs, and milk. It has triggered the digital platform provider to provide the best service for the consumers by offering the additional value aside of their main service as the competition is getting heater. They created the promotion campaign to invite their current users to use their service and tried to shift the competitor’s user. This research will help the government and the businessmen to see the insights as an opportunity for the business growth especially in the digital transformation era.